Konstribusi Mahasiswa Dalam Peningkatan Literasi Numerasi Melalui Kegiatan Kampus Mengajar di SDN 028 Balikpapan Tengah - Charisma Azizah Ibrahim; Ameliana Ameliana; Hendra Saputra Philippus; Norjannah Norjannah; Gyta Krisdiana Cahyaningrum; Didik Cahyono (Jurnal Pelayanan Masyarakat, 2024)
The campus teaching program is a form of program to build collaboration between students and teachers to support the educational process in schools. This service method is a qualitative approach. The location for community service was carried out at SDN 028 Balikpapan Tengah, participants in this activity included students and teachers. Data collection uses observation, interview and documentation techniques. The results of community service through the contribution of the 6th class of teaching campus students explained that the implementation of the program for implementing numeracy literacy included: integration of literacy, numeracy and technology adaptation (SI 3), literacy and numeracy classes, cognitive and non-cognitive assessments, adaptation technology with the theme "opening the door to the digital world", a library program with the theme "gateway to knowledge adventure", learning outside the classroom and media can improve students' literacy skills, there is an increase of 8% and numeracy has increased by 14%. So it can be concluded that the contribution of campus students to teaching can improve students' numeracy literacy at SDN 028 Balikpapan Tengah.